Transcatheter aortic valve implantation complicated by papillary muscle rupture with a good final outcome - Sorysz, Danuta; Gackowski, Andrzej; Trębacz, Jarosław; Dziewierz, Artur; Surdacki, Andrzej; Bartuś, Stanisław; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
An 88-year-old patient with a history of coronary artery bypass grafting was referred for transfemoral transcatheter aortic valve implantation (TAVI) because of severe, symptomatic (NYHA III) aortic stenosis with coexisting renal failure and other comorbidities. In echocardiogram, a severely calcified 3-cuspid aortic valve with an aortic valve area of 0.6 cm2 was noted (aortic maximal pressure gradient of 90 mm Hg and mean gradient of 46 mm Hg). The left ventricle (LV) had a small cavity and was concentrically hypertrophied (LVEDD 42 mm, IVSd 15 mm, LVEF 60%). The mitral annulus was moderately calcified. There was mild mitral regurgitation without significant stenosis (mean gradient 3.2 mm Hg, MVA 2.5 cm2). In computed tomography the aortic annulus area was 5.6 cm2. Revascularization was not required.